2017
DOI: 10.1186/s12935-017-0490-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of MARCH8, an E3 ubiquitin ligase, is associated with growth of esophageal tumor

Abstract: BackgroundHerein, for the first time, we report aberrant expression of membrane-associated RING-CH8 (MARCH8) in human esophageal squamous cell carcinoma. MARCH8 is a member of the recently discovered MARCH family of really interesting new genes (RING) E3 ligases. Though initial studies primarily focused on its immunomodulatory role, the newly discovered targets of this E3 ligase point towards its possible role in other biological processes such as embryogenesis and inhibition of apoptosis. However, its relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…Previous studies have been identified different types of proteins from blood or tumour tissues that were feasible in understanding the tumour progression in human. Some of the up/down-regulated proteins in our present study such as CNTFR, DDAH1, TUBB1, MARCH8, KRT1, KRT18, APOE, PDCD6, MMP2, ITGA6, MYOF, and TGFB2 were previously reported to be associated with certain tumorigenesis and progression in malignancies [22][23][24][25][26][27][28][29][30][31][32][33] . Taken together, these results indicated that as an oncogenic viral disease in cattle, BLV infection could alter the encapsulated sEV proteins; therefore, the new proteins are appearing within milk sEV.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies have been identified different types of proteins from blood or tumour tissues that were feasible in understanding the tumour progression in human. Some of the up/down-regulated proteins in our present study such as CNTFR, DDAH1, TUBB1, MARCH8, KRT1, KRT18, APOE, PDCD6, MMP2, ITGA6, MYOF, and TGFB2 were previously reported to be associated with certain tumorigenesis and progression in malignancies [22][23][24][25][26][27][28][29][30][31][32][33] . Taken together, these results indicated that as an oncogenic viral disease in cattle, BLV infection could alter the encapsulated sEV proteins; therefore, the new proteins are appearing within milk sEV.…”
Section: Discussionsupporting
confidence: 62%
“…MARCH5 and MARCH7 can both promote the processes of migration and invasion in ovarian cancer cells [14,15]. High expression of MARCH8 was also observed in esophageal tumors and was associated with tumor aggression [16]. However, at present, there is no evidence about the role of MARCH9 in malignancy.…”
Section: Introductionmentioning
confidence: 38%
“…The transcription of MARCH3 gene is dramatically induced by LPS and TLR8 agonist in monocytes (56). Notably, it has been demonstrated that MARCH1 is highly expressed in human hepatocellular carcinoma (HCC) cells (55), MARCH5 is up-regulated in ovarian cancer tissues (28), and MARCH8 is highly expressed in esophageal tumors and associated with tumor aggression (50). These studies suggest that certain MARCH proteins may involve in tumorigenesis.…”
Section: Properties Of the March E3 Ligase Family Membersmentioning
confidence: 99%